[3+3] Cyclocondensation of Disubstituted Biphenyl Dialdehydes: Access to Inherently Luminescent and Optically Active Hexa-substituted C3-Symmetric and Asymmetric Trianglimine Macrocycles - Wang, Zhenzhen; Nour, Hany F.; Roch, Loic M.; Guo, Minjie; Li, Wenjiao; Baldridge, Kim K.; Sue, Andrew C. -H.; Olson, Mark A. (Journal of organic chemistry, 2017)
A general synthetic route to inherently luminescent and optically active 6-fold substituted C-3-symmetric and asymmetric biphenyl-based trianglimines has been developed. The synthesis of these hexa-substituted triangular macrocycles takes advantage of a convenient method for the synthesis of symmetrically and asymmetrically difunctionalized biphenyl dialdehydes through a convergent two-step aromatic nucleophilic substitution-one-pot Suzuki-coupling reaction protocol. A modular [3+3] diamine-dialdehyde cyclocondensation reaction between both the symmetrically and asymmetrically difunctionalized-4,4'-biphenyldialdehydes with enantiomerically pure (1R,2R)-1,2-diaminocyclohexane was employed to construct the hexa-substituted triangular macrocycles. B97-D/6-311G(2d,p) density functional theory determined structures and X-ray crystallographic analysis reveal that the six substituents appended to the biphenyl legs of the trianglimine macrocycles adopt an alternating conformation not unlike the 1,3,5-alternate conformation observed for calix[6]arenes. Reduction of the imine bonds using NaBH4 afforded the corresponding 6-fold substituted trianglamine without the need to alkylate the amine nitrogen atoms which could hinder their later use as metal coordination sites and without having to introduce asymmetric carbons.